The International Comparison of Strategies for Reading Comprehension from Teacher Preference: A Review of Selected Paper - Silalahi, Novia Sariahta (Universitas Nusantara PGRI Kediri, 2019)
This paper intended to explore and giving an overview in strengths and weakness part of the proposed strategies in reading comprehension. The 18 pages article written by Scott Kissau and Florian Hiller (2013), entitled